Trend 2000 - 2003. Statistics Canada. CANSIM: Culture and Leisure - Performing and Visual Arts | Country: Canada | Province: Northwest Territories | Table: Federal government expenditures on culture, by culture activity | Variable: Arts education, Federal government capital expenditures | Units: $CAD x 1,000, 2000-2003. Data-Planet™ Statistical Ready Reference by Conquest Systems, Inc. Dataset-ID: 075-001-050. - Statistics Canada (Data-Planet™ Statistical Ready Reference by Conquest Systems, Inc., 2015)
Statistics Canada (2015). CANSIM: Culture and Leisure - Performing and Visual Arts | Country: Canada | Province: Northwest Territories | Table: Federal government expenditures on culture, by culture activity | Variable: Arts education, Federal government capital expenditures | Units: $CAD x 1,000, 2000-2003. Data-Planet™ Statistical Ready Reference by Conquest Systems, Inc. [Data-file]. Dataset-ID: 075-001-050. Dataset: Provides statistics on the performing arts in Canada, including attendance, performances, touring, employment, and financial data on performing arts companies, such as theatre, music theatre, and dinner theatre; professional orchestras; ensembles; popular music groups; individual artists and choirs; classical and contemporary dance; opera companies; and other performing companies such as circuses, ice skating shows, and variety shows. Information on visual arts includes original visual arts and crafts such as: paintings, drawings, and pastels executed entirely by hand; original engravings, prints, and lithographs; and original sculptures and statuary. CANSIM is Statistics Canada's key socioeconomic database. The datasets included here provide statistics on the Canadian population, and the nation’s resources, economy, society, and culture. In addition to conducting a Census every five years, approximately 350 active surveys are conducted on virtually all aspects of Canadian life. Statistics are provided for the nation as a whole, provinces, and other subnational geographies where available. Category: Population and Income Source: Statistics Canada Established as Canada's central statistical office by the Statistics Act of 1985, Statistics Canada is required to "collect, compile, analyse, abstract and publish statistical information relating to the commercial, industrial, financial, social, economic and general activities and conditions of the people of Canada." Its main objectives are to provide statistical information and analysis about Canada’s economic and social structure and to promote sound statistical standards and practices. http://www.statcan.gc.ca/ Subject: Performing Arts, Leisure Activities, Culture